Prevalence of hypersensitivity reactions in various forms of mastocytosis: A pilot study of 2485 adult patients with mastocytosis collected in the ECNM registry - Niedoszytko, Marek; Gorska, Aleksandra; Brockow, Knut; Bonadonna, Patrizia; Lange, Magdalena; Kluin-Nelemans, Hanneke; Oude-Elberink, Hanneke; Sabato, Vito; Shoumariyeh, Khalid; von Bubnoff, Dagmar; Müller, Sabine; Illerhaus, Anja; et al. (Allergy, 2024)
Background Hypersensitivity reactions (HR) are common in mastocytosis. However, little is known about triggers and risk factors. The registry of the European Competence Network on Mastocytosis (ECNM) enables reliable studies in a larger cohort of mastocytosis patients. We assessed prevalence, triggers and risk factors of HR in adults with mastocytosis in the ECNM registry. Methods Data were collected in 27 ECNM centers. We analyzed potential triggers (Hymenoptera venoms, food, drug, inhalant and others) and risk factors at diagnosis and during follow-up. The study group consisted of 2485 adults with mastocytosis, 1379 women (55.5%) and 1106 men (44.5%). Median age was 48.2 years (range 18-91 years). Results Nine hundred and forty eight patients (38.1%) reported one or more HR`. Most common triggers were Hymenoptera venoms in cutaneous mastocytosis (CM) and indolent systemic mastocytosis (ISM), whereas in advanced SM (advSM), most common elicitors were drugs, including nonsteroidal anti-inflammatory agents and penicillin. In multivariate analyses, tryptase level < 90 ng/mL, <15% infiltration by mast cells in bone marrow biopsy-sections, and diagnosis of ISM were identified as independent risk factors for HR. For drug-induced HR, prominent risk factors were advSM and high tryptase levels. New reactions were observed in 4.8% of all patients during 4 years follow-up. Conclusions HR are mainly triggered by Hymenoptera venoms in patients with CM and ISM and by drugs in patients with advSM. Tryptase levels <90 ng/mL, mast cell bone marrow infiltration <15%, and WHO category ISM are predictors of HR. New HR occur in 4.8% of all patients within 4 years.